Effectiveness of communication pathways and educational media in promoting nutrition-related behavioral change among mothers of toddlers: A systematic review - Nadiya Novitania Putri Diana; Nia Novita Wirawan; Widya Rahmawati (AcTion: Aceh Nutrition Journal, 2026)
Stunting remains a major public health problem in many developing countries, primarily due to inadequate nutrition. Nutrition education has been widely implemented; however, comparative evidence on the effectiveness of different communication pathways and educational media in promoting sustained maternal behavioral change remains limited. This study aimed to analyze the effectiveness of communication pathways and educational media in supporting behavior changes related to toddler nutrition. Studies were identified using the PICO framework through searches in PubMed and Scopus, following PRISMA guidelines.  The inclusion criteria were open-access articles published between 2020 and 2025 that assessed behavioral outcomes and evaluated communication pathways or educational media. The methodological quality was assessed using the Joanna Briggs Institute (JBI) critical appraisal tools. Of the 2,500 articles identified, 14 studies met the inclusion criteria. The results indicate that interpersonal communication provides the most consistent evidence to support sustained nutrition-related behavioral change through personalized two-way interactions. Community and mass communication pathways mainly improve awareness and attitudes, with less consistent effects on long-term behavior. Educational media, particularly video-based media, enhance engagement and comprehension but are most effective when integrated into interactive communication pathways. Combining communication pathways with educational media appears to be the most effective approach for improving maternal feeding practices.